Mechanism and activity of ruthenium olefin metathesis catalysts: the role of ligands and substrates from a theoretical perspective - Adlhart, Christian; Chen, Peter (Journal of the American Chemical Society, 2004)
The reaction mechanism of olefin metathesis by ruthenium carbene catalysts is studied by gradient-corrected density functional calculations (BP86). Alternative reaction mechanisms for the reaction of the "first-generation" Grubbs-type catalyst (PCy(3))(2)Cl(2)Ru=CH(2) (1) for the reaction with ethylene are studied. The most likely dissociative mechanism with trans olefin coordination is investigated for the metathesis reaction between the "first-" and the "second-generation" Grubbs-type catalysts 1 and (H(2)IMes)(PCy(3))Cl(2)Ru=CH(2) (2) with different substrates, ethylene, ethyl vinyl ether, and norbornene, and a profound influence of the substrate is found. In contrast to the degenerate reaction with ethylene, the reactions with ethyl vinyl ether and norbornene are strongly exergonic by 8-15 kcal/mol, and this excess energy is released after passing through the metallacyclobutane structure. While the metallacyclobutane is in a deep potential minimum for degenerate metathesis reactions, the energy barrier for the [2+2] cycloreversion vanishes for the most exergonic reactions. On the free energy surface under typical experimental conditions, the rate-limiting steps for the overall reactions are then either metallacyclobutane formation for 1 or phosphane ligand dissociation for 2.